Cation-deficient TiO2(B) nanowires with protons charge compensation for regulating reversible magnesium storage. (June 2020) - Luo, Lan; Zhou, Kaiqiang; Lian, Ruqian; Lu, Yanzhong; Zhen, Yichao; Wang, Jinshan; Mathur, Sanjay; Hong, Zhensheng
Abstract: Magnesium battery is a recently emerging energy storage system that has attracted considerable attention. However, its development is limited by the lack of proper electrode materials for reversible Mg 2+ intercalation/de-intercalation with satisfied capacity. Here, we firstly report easy synthesis of Ti-deficient bronze titanium dioxide nanowires by topology transformation of H-titanate precursor. It's found OH − anions substitution of O 2− supports the formation of Ti vacancies in TiO2 (B) with a high concentration, denoted as (Ti0.91 O1.64 (OH)0.36 ), and can be utilized as a robust host for Mg-ion storage. Both the theoretical and experimental study revealed that Ti-deficient TiO2 (B) exhibits much improved electronic properties with unpaired electrons. Density functional theory (DFT) calculations also reveal Ti vacancies provide more feasible binding sites for Mg-ion. More importantly, it's surprisingly found the presence of protons enables a suitable binding energy for Mg-ion intercalation and extraction. As a result, such material displays discharge and charge capacities of 217.3 and 165.3 mA h g −1 at 0.02 A g −1, representing the highest value among the reported Ti-based electrode materials as well as a high initial Columbic efficiency up to 76.1%. This study gives a new and in-depth view on how cation-deficient structure regulates and promotes the reversible energy storage. Graphical abstract: Image 1 Highlights: Ti-deficient TiO2 (B) was firstly prepared by topology transformation of H-titanate. OH − substitution of O 2− supports the formation of plentiful Ti vacancies. Theoretical and experimental study reveal significantly improved electronic properties. A large discharge capacity of 217.3 mA h g −1 and a high ICE of 76.1% for Mg battery are obtained. Charge compensated protons enables a suitable binding energy for Mg-ion intercalation and extraction.